Inovasi Jajanan Pasar sebagai Dessert Hotel Berbasis Kesehatan dan Estetika di Gumaya Tower Hotel Semarang - Safitri, Dona Ayu; Yuliamir, Henry (Mahesa Research Center, 2025)
Abstract Revitalization of traditional snacks as healthy and aesthetic desserts is an innovative strategy in strengthening local culinary identity in the hospitality industry. This study aims to examine the process of modifying traditional market snacks to meet the aesthetic and health standards of five-star hotels, with a case study at Gumaya Tower Hotel Semarang. The approach used is descriptive qualitative with a single case study method. Data were collected through in-depth interviews, participatory observation, and documentation of chefs, food and beverage managers, and hotel guests. The results of the study indicate that innovation is carried out through substituting unhealthy ingredients with natural ingredients, modern serving techniques, and inserting local cultural values through storytelling. Hotel guest responses showed a high level of satisfaction with the visual appearance and health value, although some noted a change in taste from the traditional version. This revitalization also has a positive impact on the hotel's image, strengthens product differentiation, and supports the preservation of Nusantara culinary culture. These findings are important as a basis for developing sustainable culinary innovations based on local wisdom and can be applied in other hospitality industries.